Has Chinese aid benefited recipient countries? - Mandon, Pierre,Woldemichael, Martha Tesfaye (International Monetary Fund, 2022)
This paper employs a meta-regression analysis of 473 estimates from 15 studies to take stock of the empirical literature on Chinese aid effectiveness. After accommodating publication selection bias, we find that, on average, Beijing's foreign assistance has had a positive impact on economic and social outcomes in recipient countries but an opposite effect on governance, albeit negligible in size. We also show that (i) studies that fail to uncover statistically significant effects are less likely to be submitted to journals, or accepted for publication; and (ii) results are not driven by authors' institutional affiliation. Differences in study characteristics such as the type of development outcome considered, how the Chinese aid variable is measured, the geographic region under study, and publication outlet explain the heterogeneity among Chinese aid effectiveness estimates reported in the literature
10.5089/9798400200670.001
Keywords: Graue Literatur; China; meta-regression analysis; Econometric and Statistical Methods; Economic Development and Innovation; Foreign Aid and Meta-Regression Analysis; Publication Selection Bias; Technological Change and Growth; foreign aid; Foreign Aid; Exports and Imports; Econometric and Statistical Methods: Other; Economic Development; Innovation; Technological Change; and Growth; Investment; Capital; Intangible Capital; Capacity; Economic & financial crises & disasters; Economics of specific sectors; International economics; Macroeconomics; Economics: General; Development assistance; Infrastructure; National accounts; Currency crises; Informal sector; Economics; International relief; Saving and investment